Fat persons’ suffering in the search for health care: reports of a YouTube activist against fatphobia (Research, Society and Development, 2021)
The debate on fatphobia and its confrontations has been growing in Brazil, getting millions of followers together on different platforms. The aim of this study is to analyze the arguments present in the discourse of a cyberactivist channel against fat phobia, focusing on narratives about food and relationships with workers and health services. Methodology:This is a qualitative study on YouTube, carried out using the “Bernardo Fala” channel, one important representative of this form of cyberactivism in Brazil. Argument analysis, according to Toulmin's perspective, was adopted as a method for understanding the argumentative structures used by the YouTuber. Results: The main theses point to weight as an insufficient predictor of health and the embarrassment suffered by fat persons receiving health care. Conclusion: The work showed, in the argument structures, a common debate of fat cyberactivism that converges to the need for investment in the education and training of health workers and in the structures of health care provided to fat persons.